ANALISIS IMPLEMENTASI DISIPLIN PNS SEBAGAI INSTRUMEN MANAJEMEN PNS DI PTUN SURABAYA - Nadia Faizah Putri Devina; Adhitya Widya Kartika (Jurnal Ilmiah Advokasi, 2026)
Civil servants (PNS) are state apparatuses who play a strategic role in the implementation of public services, including supporting judicial functions at the Surabaya Administrative Court (PTUN Surabaya). In this context, the enforcement of civil servant discipline serves as a crucial instrument in realizing effective, professional, and accountable human resource management. This study aims to analyze the implementation of civil servant discipline in supporting personnel management at PTUN Surabaya, as well as to identify the supporting and inhibiting factors. This research employs an empirical juridical method with a qualitative approach, where data are collected through observation and interviews and analyzed using a descriptive-analytical framework. The findings indicate that the implementation of civil servant discipline at PTUN Surabaya has been relatively effective, as reflected in internal policies and work programs developed by the Subdivision of Personnel, Organization, and Governance. These programs include attendance monitoring, performance supervision, and the strengthening of a discipline-based work culture. However, this study also identifies several challenges in implementation, such as the lack of continuous supervision and variations in compliance levels among employees. The main contribution of this research lies in identifying an effective discipline implementation model based on internal work programs that enhance the quality of personnel management, while also emphasizing the importance of strengthening supervision and consistent capacity-building measures. Therefore, civil servant discipline functions not only as a control mechanism but also as a fundamental pillar in building professional and integrity-based personnel management within PTUN Surabaya.Keywords: Civil Service, Civil Servants, Discipline, Personnel Management, Administrative Court